DUAL STAINING IDENTIFIES A GREATER PROPORTION OF MORIBUND SPERMATOZOA IN STALLION SEMEN WITH POOR CRYOTOLERANCE - PAUL, NILENDU; TALLURI, T R; YASHPAL; LEGHA, R A; NAG, PRADEEP; KUMARESAN, ARUMUGAM (The Indian Journal of Animal Reproduction, 2023)
The present study was conducted to evaluate the functional membrane integrity of cryopreserved spermatozoa from stallions belonging to two contrasting motility groups (high and low motility groups). A dual staining method comprising of carboxy fluoroscein diacetate (CFDA) and propidium iodide (PI) was used for this purpose. Stallions were classified into either high (post thaw progressive motility e”35%) or low (post thaw progressive motility <25%) motility groups. The proportion of membrane intact spermatozoa was significantly (P<0.05) higher in high motility group. Interestingly, it was observed that the proportion of moribund population was significantly (P<0.05) higher in low motility group as compared to high motility group. It was inferred that higher proportion of moribund spermatozoa might be one of the important contributing factors for poor sperm motility in stallions belonging to low motile group.